ANALISIS PERBANDINGAN FAKTOR-FAKTOR YANG MEMPENGARUHI LIKUIDITAS PADA INDUSTRI PERTANIAN, KEHUTANAN DAN PERIKANAN, DAN INDUSTRI OTOMOTIF - Dhian Andanarini Minar Savitri; Harum Indinah Dianingsih (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2015)
The purpose of this research is to know how the sales growth, accountreceivables turn over and working capitals turnover impact the liquiditylevel at agro industry and automotive industry which listed on Bursa EfekIndonesia (2010-2015). The datas in this research is analyzed fromfinancial statement of the companies. The datas which have alreadycollected are processed with classic assumption test before hypothesis testand chow test.Hypothesis datas in this research uses double degree linear regressionwith t test and chow test. The research show that sales growth doesn”t hasimpact toward liquidity level partially, receivables turn over has impacttoward liquidity level partially, working capital turnover has impact onagro industry but doesn’t impact on automotive industry. While the testcan use the chow test to know that there is no dofference between the salesgrowth, account receivables turnover and working capital turnover of thecompany’s liquidity in the agro industry and automotive industry